Unbroken : a World War II airman's story of survival, resilience, and redemption - Hillenbrand, Laura (Random House Trade Paperbacks, 2014)
On a May afternoon in 1943, an Army Air Forces bomber crashed into the Pacific Ocean and disappeared, leaving only a spray of debris and a slick of oil, gasoline, and blood. Then, on the ocean surface, a face appeared-- Lt. Louis Zamperini. Captured by the Japanese and driven to the limits of endurance, Zamperini would answer desperation with ingenuity; suffering with hope, resolve, and humor.